Comparative Price Trend Studies of Five Commercially Important Timber Species Logs-Narainpur Depot (Madhya Pradesh) - Suri, S. K. (Indian Forester, 1973)
Based on the analysis of auction results, the price trends of second grade timber logs of Teak (Tectona grandis). Sal (Shorea robusta), Bija (Pterocarpus marsupium), Haldu (Abina cordifolia) and Saja (Terminalia tomentosa) have been discussed and compared. It has been concluded that Teak logs fetch a much higher prices per m5 as compared to logs of other species. There is a definite trend in price incetase with increase om girth for all species. Compared to Teak, the average prices of Sal, Bija, Haldu and Saja logs are 30%, 45%. 17% and 12% of Teak respectively.